Penguatan Gotong Royong Sebagai Wujud Pengabdian Membangun Kebersamaan di Tengah Masyarakat - Hambali, Muhammad Imam (Yayasan Kawanad, 2026)
Community service is a form of sustainable empowerment aimed at improving quality of life and strengthening the collective character of society. One of the core cultural values underlying this activity is gotong royong (mutual cooperation), which has long served as a social identity of the Indonesian nation. However, modernization and the rise of individualism have led to a decline in the practice of gotong royong in social life. Therefore, this community service program seeks to revitalize the spirit of gotong royong by involving students and community members in environmental cleanliness activities. The method applied is Participatory Action Research (PAR), which includes observation, participatory discussions, environmental clean-up actions, and joint evaluation. The results indicate an increased level of public awareness regarding the importance of environmental cleanliness, the emergence of active community participation, and the establishment of effective collaboration among students, local residents, and the government as a facilitating institution. In addition to creating a cleaner, more organized, and healthier environment, this activity also strengthens values of togetherness, social care, and collective responsibility as social capital in preventing environmental problems such as flooding. This community service initiative not only contributes to physical environmental improvement but also plays a significant role in fostering sustainable ecological behavior and revitalizing the value of gotong royong within society.